Chemical stability and electrical and mechanical properties of BaZrxCe0.8-xY0.2O3 with CeO2 protection method. (24th August 2017) - Jhuang, Jhe-Wei; Lee, Kan-Rong; Chang, Jeng-kuei; Shen, Chin-Tien; Lee, Yi-Hsuan; Lee, Sheng-Wei; Tseng, Chung-Jen
Abstract: This study investigated the decline in the conductivity and mechanical strength after CO2 poisoning and found a new protective method for BaZrx Ce0.8-x Y0.2 O3 proton-conducting electrolyte. The high temperature solid state reaction (SSR) was used in synthesizing electrolyte to naturally generate CeO2 on the surface. A comparison of the oxides in the conductivity decline test revealed that the sample with CeO2 on the surface substantially improved the stability of conductivity, reducing the decline ratio from 56% to 7% for BCY electrolyte and 50% to 7% for BCZY sample. Raman mapping results indicate the naturally generated CeO2 on electrolyte surface can considerably reduce impurity formation and maintain the microstructure of electrolyte. This work demonstrates that samples with CeO2 on the surface effectively protect the BaCeO3 -based proton-conducting electrolyte from CO2 poisoning. This method may be applied to similar BaCeO3 -based perovskite materials as a new protective method. Highlights: Processing conditions were found that naturally generates CeO2 on BCY oxide surface. Stabilities of various composition samples for CO2 poisoning were investigated. Surface CeO2 reduces conductivity decline ratio from 56% to 7% for BCY oxide. Surface CeO2 reduces hardness decline ratio from 39% to 10% for BCY oxide.